AHP 35: Review: RE-CONSTRUCTED ANCESTORS AND THE LAHU MINORITY IN SOUTHWEST CHINA - Du, Shanshan (Asian Highlands Perspectives, 2018)
Written in Chinese, Re-Constructed Ancestors: The Mobilization of Ethnic Groups in [China's] Southwest Frontier and the Construction of Lahu History, consists of an Introduction, Conclusion, and five chapters. Following a critical review of the literature, in the Introduction, Ma presents his groundbreaking analytical framework and methodologies concerning the ethno-history of southwest China, and the history of the Lahu in particular. ...